Phosphor-Doped Thermal Barrier Coatings Deposited by Air Plasma Spray for In-Depth Temperature Sensing - Peng, Di (Sensors (Basel), 2016)
Yttria-stabilized zirconia (YSZ)-based thermal barrier coating (TBC) has been integrated with thermographic phosphors through air plasma spray (APS) for in-depth; non-contact temperature sensing. This coating consisted of a thin layer of Dy-doped YSZ (about 40 µm) on the bottom and a regular YSZ layer with a thickness up to 300 µm on top. A measurement system has been established; which included a portable; low-cost diode laser (405 nm); a photo-multiplier tube (PMT) and the related optics. Coating samples with different topcoat thickness were calibrated in a high-temperature furnace from room temperature to around 900 °C. The results convincingly showed that the current sensor and the measurement system was capable of in-depth temperature sensing over 800 °C with a YSZ top layer up to 300 µm. The topcoat thickness was found to have a strong effect on the luminescent signal level. Therefore; the measurement accuracy at high temperatures was reduced for samples with thick topcoats due to strong light attenuation. However; it seemed that the light transmissivity of YSZ topcoat increased with temperature; which would improve the sensor’s performance at high temperatures. The current sensor and the measurement technology have shown great potential in on-line monitoring of TBC interface temperature.